2001
DOI: 10.1177/109019810102800605
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Social Cohesion and Empowerment: Support and New Implications for Theory

Abstract: Empowerment theory represents an expansive view of individual and collective behavior that includes the active participation of individuals and groups in altering and shaping the socioenvironmental context. Critical to health educators are local interventions that yield participation of community members and empowerment for participants. The concept of social cohesion embraces participation but expands this behavioral emphasis to incorporate notions of trust, connectedness, and civic engagement. This study pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 44 publications
9
99
0
2
Order By: Relevance
“…Although other conceptual frameworks and operational definitions of empowerment exist (Becker, Israel, Schulz, Parker, & Klem, 2002;Frymier, Shulman, & Houser, 1996;Hardiman & Segal, 2003;Israel, Checkoway, Schulz, & Zimmerman, 1994;Kim, Crutchfield, Williams, & Hepler, 1998;Matthews, Diaz, & Cole, 2003;Segal, Silverman, & Temkin, 1995;Spreitzer, 1995;Wallerstein, 1992Wallerstein, , 2002, the Sociopolitical Control Scale (SPCS) (Zimmerman & Zahniser, 1991) has been widely used in studies of the construct (e.g., Carballo-Dieguez et al, 2005;Hamilton & Fauri, 2001;Holden, Crankshaw, Nimsch, Hinnant, & Hund, 2004;Holden et al, 2005;Itzhaky, 2003;Itzhaky & York, 2000Peterson & Hughey, 2004;Peterson & Reid, 2003;Speer, 2000;Speer, Jackson, & Peterson, 2001;Speer & Peterson, 2000;Smith & Propst, 2001, Zimmerman, Ramirez-Valles, Suarez, de la Rosa, & Castro, 1997. Itzhaky and York (2003), for instance, translated the SPCS into Hebrew to study PE among immigrants participating in community development activities in Israel.…”
mentioning
confidence: 99%
“…Although other conceptual frameworks and operational definitions of empowerment exist (Becker, Israel, Schulz, Parker, & Klem, 2002;Frymier, Shulman, & Houser, 1996;Hardiman & Segal, 2003;Israel, Checkoway, Schulz, & Zimmerman, 1994;Kim, Crutchfield, Williams, & Hepler, 1998;Matthews, Diaz, & Cole, 2003;Segal, Silverman, & Temkin, 1995;Spreitzer, 1995;Wallerstein, 1992Wallerstein, , 2002, the Sociopolitical Control Scale (SPCS) (Zimmerman & Zahniser, 1991) has been widely used in studies of the construct (e.g., Carballo-Dieguez et al, 2005;Hamilton & Fauri, 2001;Holden, Crankshaw, Nimsch, Hinnant, & Hund, 2004;Holden et al, 2005;Itzhaky, 2003;Itzhaky & York, 2000Peterson & Hughey, 2004;Peterson & Reid, 2003;Speer, 2000;Speer, Jackson, & Peterson, 2001;Speer & Peterson, 2000;Smith & Propst, 2001, Zimmerman, Ramirez-Valles, Suarez, de la Rosa, & Castro, 1997. Itzhaky and York (2003), for instance, translated the SPCS into Hebrew to study PE among immigrants participating in community development activities in Israel.…”
mentioning
confidence: 99%
“…Predictors: The five predictor measures were based on scales used in previous studies-i.e., attributions of drug abuse [40]; perceived neighbourhood incivilities [41]; awareness of the extent of neighbourhood substance abuse problem [13]; and concern with violence victimization and perceived police responsiveness to drug crime [35]. Table 1: Demographic characteristics of participants.…”
Section: Methodsmentioning
confidence: 99%
“…The attributions of drug abuse measure were based on a nine-item, five-point Likert-type scale [40], which examined the extent respondents agreed or disagreed with statements focusing on internal, individual-level causes of drug abuse (e.g., Drug abuse is caused by individuals with problems, not communities with problems) or external, community-level causes of drug abuse (e.g., The only way to really prevent people from abusing drugs is to improve things like housing and the local economy). Internal attribution items were recoded so that higher scores on the scale indicated higher external attributions of substance abuse (Cronbach α=0.68).…”
Section: N=283mentioning
confidence: 99%
“…13 studies like that conducted by RĂŒsch et al (2009: 552) which concluded that greater self-stigma could be related to reduced willingness to communicate for help, 'possibly leading to decreased coping resources and thus to psychiatric hospitalisation as a last resort.' This calls for initiatives aimed at challenging self-stigma, such as the training and empowerment of mental health consumers by health educators (Speer et al 2001).…”
Section: Teh King Watson and Liumentioning
confidence: 99%